Aerosol Modulation of Ultraviolet Radiation Dose over Four Metro Cities in India. (2nd January 2014) - Panicker, A. S.; Pandithurai, G.; Beig, G.; Kim, Dongchul; Lee, Dong-In
Abstract : This paper discusses the influence of aerosols on UV erythemal dose over four metro cities in India. Tropospheric Emission Monitoring Internet Service (TEMIS), archived UV-index (UV-I), and UV daily erythemal dose obtained from SCIAMACHY satellite were used in this study during June 2004 and May 2005 periods covering four important Indian seasons. UV-Index (UV-I), an important parameter representing UV risk, was found to be in the high to extreme range in Chennai (8.1 to 15.33), moderate to extreme range in Mumbai and Kolkata (5 to 16.5), and low to extreme over Delhi (3 to 15). Average UV erythemal dose showed seasonal variation from 5.9 to 6.3 KJm −2 during summer, 2.9 to 4.4 KJm −2 during postmonsoon, 3 to 4.5 KJm −2 during winter, and 5.1 to 6.19 KJm −2 during premonsoon seasons over the four cities. To estimate the influence of aerosols on reducing UV dose, UV aerosol radiative forcing and forcing efficiency were estimated over the sites. The average aerosol forcing efficiency was found to be from - 1.38 ± 0.33 to - 3.01 ± 0.28  KJm −2 AOD −1 on different seasons. The study suggests that aerosols can reduce the incoming UV radiation dose by 30–60% during different seasons.